Office-based endoscopic surgery for benign, premalignant, and malignant laryngeal lesions - Petru Gurău; Oleg Arnaut; Eusebiu Sencu; Dumitru Sofroni (The Egyptian Journal of Otolaryngology)
Abstract Background The available publications concerning office-based flexible endoscopic laryngeal surgery (OBFELS) are mostly dedicated to managing benign and premalignant laryngeal lesions using angiolytic lasers. There is a lack of information about using other lasers and different treatment approaches in OBFELS. There is also a lack of publications related to OBFELS for malignant laryngeal lesions. The objective of the study was to share our experience in OBFELS using Nd:YAG laser, 980/1470 nm diode laser, diathermy snare, and biopsy forceps for benign, premalignant, and malignant laryngeal lesions, and to evaluate the effectiveness of the treatment. Methods OBFELS was performed in 362 patients from 3 groups: benign lesions (BL) (n = 285), represented by nodules, polyps, Reinke`s edema (RE), nonspecific granulomas, cysts, and neurofibroma; premalignant lesions (n = 53), represented by laryngeal papilloma/papillomatosis (LP), and hyperplastic laryngeal lesions (HLL), including chronic hyperplastic laryngitis with keratosis, leukoplakia, pachydermia, and verrucous neoplasia; and malignant lesions, represented by primary T1-T2 glottic carcinoma (n = 24). All endoscopic interventions were performed with spontaneous breathing under topical anesthesia without sedation or with minimal/moderate intravenous sedation/analgesia. The following endoscopic techniques in different combinations were used for lesion eradication: cold surgery by flexible forceps, diathermy snare excision, and laser ablation/vaporization using Nd:YAG laser (1064 nm) or 980 nm diode laser. Results Complete eradication/removal of visible lesions was obtained in all treated cases. Recurrent lesions were registered in the BL group in 2.8%, in the LP group – in 33.3%, in the HLL group – in 6.9%, and in the glottic carcinoma group – in 4.2% of cases. Larynx preservation was obtained in all the patients, and ultimate disease control by OBFELS alone was achieved in 79.2% of patients with glottic carcinoma. Conclusions OBFELS using Nd:YAG laser, 980 nm diode laser, diathermy snare, and flexible biopsy forceps can be considered an alternative to traditional OR endoscopic laryngeal surgery for benign, premalignant, and malignant laryngeal lesions in selected patients. The proposed techniques allow for overcoming some limits of previously proposed methods and demonstrate the applicability of OBFELS even for bulky lesions and primary malignant lesions, especially in patients with risks and contraindications for general anesthesia and direct laryngoscopy.